Decreased Frequencies of Th17 and Tc17 Cells in Patients Infected with Avian Influenza A (H7N9) Virus - Jiaqi Bao; Dawei Cui; Xiaochen Wang; Qianda Zou; Dejian Zhao; Shufa Zheng; Fei Yu; Li Huang; Yuejiao Dong; Xianzhi Yang; Guoliang Xie; Weizhen Chen; et al. (Journal of Immunology Research)
The outbreak of avian influenza A (H7N9) virus infection, with a high mortality rate, has caused concern worldwide. Although interleukin-17- (IL-17-) secreting CD4+ T (Th17) and CD8+ T (Tc17) cells have been proven to play crucial roles in influenza virus infection, the changes and roles of Th17 and Tc17 cells in immune responses to H7N9 infection remain controversial. In this study, we found that the frequencies of Th17 and Tc17 cells among human peripheral blood mononuclear cells (PBMCs) as well as IL-17A protein and mRNA levels were markedly decreased in patients with acute H7N9 virus infection. A positive correlation was found between the serum IL-17A level and the frequency of these two cell groups. In vitro infection experiments revealed decreased Th17 and Tc17 cell frequency and IL-17A levels at various time points postinfection. In addition, Th17 cells were the predominant sources of IL-17A in PBMCs of patients infected with H7N9 virus. Taken together, our results indicate immune disorder in acute H7N9 infection and a restored Th17 and Tc17 cell frequency might serve as a biomarker for predicting recovery in patients infected with this virus.